Re-actualization of Javanese Ethical Values in Contextual Church Missions in the Samironobaru Javanese Christian Church - Sri Dwi Harti; David Ming; Daud Alfons Pandie; Agus Sanjaya; Sukamto Sukamto (Sekolah Tinggi Theologia Jaffray, 2023)
This study aims to interpret the ethical values of the Javanese community in the contextual mission of the church in the context of shifting ethical values in society today due to globalization and dynamic social changes in society. The ethical values of the Javanese community which are correlated with the church's mission contextually tend to become degraded in the reality of social change in today's society. Using a qualitative method, this research was conducted at the Samironobaru Javanese Christian Church and found that in an effort to contextualize the church's mission, the church in the context of Javanese society needs to actualize the ethical values of the Javanese community in a contextual church mission approach.